Concise history of Indian economy - "Bhattacharyya, Dhires" (New Delhi, 1989)
This book the following topics Trade under the East India company; Economic ''drain'' from India; Revenue administration under the East India company; Economic transition in India, Famines and famine relief; Agriculture and agricultural policy under British rule; State aid to industry; A history of modern industrial development; Industrial organisation, entrepreneurship and capital; A history of India's foreign trade and trade policies; Transport and communication; Labour legislation and trade union movement; A history of Indian currency; Banking development in India; Government finance; National income etc
Keywords: India economic policy